Mesoscopic Self-Assembly: A Shift to Complexity - Mastrangeli, Massimo (Frontiers in Mechanical Engineering, 2015)
By focusing on the construction of thermodynamically stable structures, the self-assembly of mesoscopic systems has proven capable of formidable achievements in the bottom-up engineering of micro- and nanosystems. Yet, inspired by an analogous evolution in supramolecular chemistry, synthetic mesoscopic self-assembly may have a lot more ahead, within reach of a shift toward fully three-dimensional architectures, collective interactions of building blocks and kinetic control. All over these challenging fronts, complexity holds the key.